FREQUENCY OF GENERALIZED ANXIETY DISORDERS IN PATIENTS WITH POLYCYSTIC OVARIAN SYNDROME - Asghar, Rabia; Zubair, Usama Bin; Ali, Syed Azhar; Khan, Ayaz Muhammad; Shafi, Aneel; Ahmad, Hafiz Shafique (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the factors associated with generalized anxiety disorders in patients presenting with polycystic ovarian syndrome. Study Design: Cross-sectional study. Place and Duration of Study: Gynecology and Psychiatric outpatient department of Pakistan Institute of Medical Sciences, SZABMU, Islamabad, from Jan to Jul 2016. Methodology: Patients presenting with polycystic ovarian syndrome were enrolled. Patients were selected from the gynaecological and Medicine department. Patient’s history was taken and diagnosis of generalized anxiety disorder was made utilising Generalized Anxiety Disorder-7. Patients having diabetes mellitus, hypertension, Cushing’s syndrome, hypoglycaemia, co-morbid psychiatric illnesses, history of psychiatric illness in past and family history of psychiatric illness were excluded from the study. Results: Among 105 patients with polycystic ovarian syndrome, 79 (75%) patients had no generalized anxiety disorders while, 26 (25%) had generalized anxiety disorders. 2 out of 12 (16.6%) patients of age range of 15-20 year had generalized anxiety disorders, 9 out of 63 14.2% patients having age 21-30 years had generalized anxiety disorders and 15 out of 30 (50%) patients having age 31-40 years age had generalized anxiety disorders. Chi-square test revealed age, education level and socioeconomic status has a significant association with presence of generalized anxiety disorder among patients of polycystic ovarian disorder (with p-value <0.05). Conclusion: Generalized anxiety disorder was common in patients with polycystic ovarian syndrome. Age, low education level and low socioeconomic status had a significant relationship with generalized anxiety disorder in polycystic ovarian syndrome patients.